2020
DOI: 10.3233/shti200718
|View full text |Cite
|
Sign up to set email alerts
|

Creating Synthetic Patients to Address Interoperability Issues: A Case Study with the Management of Breast Cancer Patients

Abstract: Interoperability issues are common in biomedical informatics. Reusing data generated from a system in another system, or integrating an existing clinical decision support system (CDSS) in a new organization is a complex task due to recurrent problems of concept mapping and alignment. The GL-DSS of the DESIREE project is a guideline-based CDSS to support the management of breast cancer patients. The knowledge base is formalized as an ontology and decision rules. OncoDoc is another CDSS applied to breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In the present study, the results showed that the experimental group had a lower incidence of adverse reactions, suggesting that the whole case management model contributes to lower postoperative adverse reactions in breast cancer patients. It is presumably due to the fact that the one-to-one case management boosts the patient's selfconfidence in disease management, thereby promoting the recovery of the patient's body function, improving the patient's self-efficacy and self-management behavior, and thus lowering the incidence of postoperative adverse reactions in cancer patients [16]. As previously noted, surgical trauma, disease recurrence, anxiety, and uncertainty of prognosis adversely affect the patients physiologically and psychologically, thereby compromising the patient's treatment compliance [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the results showed that the experimental group had a lower incidence of adverse reactions, suggesting that the whole case management model contributes to lower postoperative adverse reactions in breast cancer patients. It is presumably due to the fact that the one-to-one case management boosts the patient's selfconfidence in disease management, thereby promoting the recovery of the patient's body function, improving the patient's self-efficacy and self-management behavior, and thus lowering the incidence of postoperative adverse reactions in cancer patients [16]. As previously noted, surgical trauma, disease recurrence, anxiety, and uncertainty of prognosis adversely affect the patients physiologically and psychologically, thereby compromising the patient's treatment compliance [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a tumor size of "more than 4cm" would have two possible correspondences, T2 (more than 4 cm but less than 5 cm) and T3 (more than 5 cm). To solve this interoperability issue, for each OncoDoc patient, we generated potential corresponding DESIREE synthetic patients [4].…”
Section: Creation Of Oncodoc-derived Synthetic Patientsmentioning
confidence: 99%
“…As the two CDSSs make use of two different domain knowledge models and two different formalisms to represent breast cancer data and CPGs, we developed and implemented a model transformation from OncoDoc to DESIREE to be able to evaluate the GL-DSS with data generated from OncoDoc. Because one-to-one matching between the domain knowledge concepts of OncoDoc and DESIREE could not systematically be performed, we created "synthetic" patients to translate OncoDoc clinical cases in the DESIREE formalism [4]. Going further in the evaluation of the DESIREE GL-DSS, the aim of this paper is to describe the enrichment of the DESIREE ontology to integrate OncoDoc concepts, how the inference engine of the GL-DSS was used to implement the model transformation, and the results of the evaluation of the DESIREE GL-DSS.…”
Section: Introductionmentioning
confidence: 99%
“…There have been prior attempts to create synthetic health data that focus on interoperability [8,17] as well as work that attempted to enrich such data with de-identified time-series data (e.g., ECGs recorded in an ICU) [18] and work that linked together synthetic brain imagery phenotypes and synthetic genomic data to address the complexity of real health data that exist in various forms [13].…”
Section: Introductionmentioning
confidence: 99%